Зміна швидкісних характеристик автобусного маршруту у різні періоди доби - Євчук, Юрій; Плесак, Степан; Корик, Яна (Видавництво Львівської політехніки, 2018)
Studies are directed to know the change the speed characteristics of the bus route at different periods of the day. The data obtained can be very useful in assessing the need for additional priorities in public transport in the central parts of cities.
Changing speed characteristics of bus routes across many dayparts
Keywords: 656.13